Parallel computing and quantum chromodynamics - Bowler, Kenneth C.; Hey, Anthony J.G. (Parallel computing, 1999)
The study of Quantum Chromodynamics (QCD) remains one of the most challenging topics in elementary particle physics. The lattice formulation of QCD, in which space–time is treated as a four-dimensional hypercubic grid of points, provides the means for a numerical solution from first principles but makes extreme demands upon computational performance. High Performance Computing (HPC) offers us the tantalising prospect of a verification of QCD through the precise reproduction of the known masses of the strongly interacting particles. It is also leading to the development of a phenomenological tool capable of disentangling strong interaction effects from weak interaction effects in the decays of one kind of quark into another, crucial for determining parameters of the Standard Model of particle physics. The 1980s saw the first attempts to apply parallel architecture computers to lattice QCD. The SIMD and MIMD machines used in these pioneering efforts were the ICL DAP and the Cosmic Cube, respectively. These were followed by the Connection Machine, the Meiko i860 Computing Surface and the Intel Hypercube. The end of the decade witnessed a rise in the development of special purpose dedicated parallel systems, notably the APE machines in Rome, the Columbia machines, the GF-11 system at IBM Research and the QCDPAX project in Tsukuba. The state-of-the-art is represented by the CP–PACS machine at Tsukuba, and QCDSP, the latest Columbia machine. We give a brief pedagogic review of lattice QCD, outline the computational methodology used and discuss the sources of systematic error that arise in numerical calculations. We outline some of the early calculations and discuss parallel architectures and their application to QCD, giving examples of both commercial and special purpose machines. After a short section on recent developments, we describe state-of-the-art machines and conclude with the prospects for the future.